A microfluidic organic transistor for reversible and real-time monitoring of H2O2 at ppb/ppt levels in ultrapure water. Issue 38 (13th April 2022) - Ohshiro, Kohei; Sasaki, Yui; Zhou, Qi; Didier, Pierre; Nezaki, Takasuke; Yasuike, Tomoharu; Kamiko, Masao; Minami, Tsuyoshi
Abstract : A microfluidic organic transistor functionalized with phenyboronic acid could monitor not only a reversible boronate anion with H2 O2 but also an irreversible conversion into a phenol structure by a continuous flow. Abstract : A microfluidic organic transistor functionalized with phenylboronic acid firstly succeeded in reversible and real-time monitoring of H2 O2 at ppb/ppt levels in ultrapure water, which would be used not only as portable chemical sensors but also as monitoring tools to clarify unknown reaction mechanisms of phenylboronic acid with H2 O2 .